The management of rural tourism in Barru Regency from a supply and demand perspective - Ilham Junaid; Muhammad Dzakwan Mufadhdhal Ilham; Rika Lisa Riani; Andi Fikanisa Fiarta; Putri Rizkiyah (Masyarakat, Kebudayaan dan Politik, 2023)
There is limited literature on the study of rural tourism, particularly related to supply and demand. This study aims to (1) identify the supply and demand aspects of rural tourism, (2) describe the concept of rural tourism based on supply and demand data. This research employs a qualitative approach in examining rural tourism in Paccekke Village, Barru Regency, for six months in the period from April to September 2021. The authors collected information through interviews with the local community and authority of Paccekke Tourism Village and direct observation. The study reveals that local communities and village officials have the opportunity to manage and develop villages through the concept of rural tourism. There are three types of supply: existing potential supply, supply of tour packages, and alternative tourism supply. This paper divides the demand for rural tourism into two parts, including products that can meet the tourists’ needs and prepared and managed rural tourism products. This study concludes that rural tourism can be realised by combining the concepts of supply and demand. This study contributes to the management and development of the village through the concept of rural tourism. This research strengthens the theory/concept of supply and demand in examining the reality of rural tourism development.